2015
DOI: 10.1212/wnl.0000000000001938
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lp-PLA 2 -A and early recurrence of vascular events after TIA and minor stroke

Abstract: Higher levels of Lp-PLA2-A in the acute period are associated with increased short-term risk of recurrent vascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 22 publications
(21 reference statements)
3
36
0
2
Order By: Relevance
“…Recently, in the Clopidogrel in High-Risk Patients with Acute Non-disabling Cerebrovascular Events trial, Chinese patients, who experienced a transient ischemic attack or minor stroke, exhibited a positive association between increased Lp-PLA 2 levels and the short-term risk of ischemic events [9]. In addition, Lp-PLA 2 activity might be a useful tool for identifying patients with intracranial large-artery occlusive disease who are at higher risk of suffering new vascular events [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in the Clopidogrel in High-Risk Patients with Acute Non-disabling Cerebrovascular Events trial, Chinese patients, who experienced a transient ischemic attack or minor stroke, exhibited a positive association between increased Lp-PLA 2 levels and the short-term risk of ischemic events [9]. In addition, Lp-PLA 2 activity might be a useful tool for identifying patients with intracranial large-artery occlusive disease who are at higher risk of suffering new vascular events [13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the individual roles of endothelial dysfunction and inflammation in intracranial atherosclerotic stroke (ICAS) remain unknown. Most previous studies reported an association between endothelial dysfunction or inflammation and clinical events, including stroke recurrence, in stroke patients; however, there have been few reports concerning patients with ICAS [6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…These findings strongly support that Lp-PLA2 plays important roles in the pathophysiological and clinical manifestations of cerebrovascular diseases. [1819] This paper revealed, from performing logistic regression analysis toward the 8 risk factors in 88 cases of ischemic cerebrovascular events, 4 significant independent risk factors toward stroke in EH patients, among which Lp-PLA2 is the most important independent risk factor ( OR : 13.699, 95% CI : 5.236–35.837, P < 0.0001), with B ’ as 0.708, indicating its highest risk toward stroke. The occurrence of stroke in EH patients with Lp-PLA2 ≥358.33 μg/L was 13.6 times than those with Lp-PLA2 < 358.33 μg/L, indicating that Lp-PLA2 is an important independent risk factor toward ischemic cerebrovascular events.…”
Section: Discussionmentioning
confidence: 94%
“…29 Furthermore, the results of the investigation of large clinical samples show that higher levels of Lp-PLA2 in the acute period are associated with increased short-term risk of recurrent vascular events. 30 To our knowledge, atherosclerosis is a chronic inflammation associated with increased expression of the acute-phase isoforms of SAA. SAA is a plasma biomarker for future cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%